REDESAIN RUMAH SAKIT UMUM DAERAH OTANAHA DENGAN PENDEKATAN ARSITEKTUR BERKELANJUTAN - Monoarfa, Aderival Fidyanto; Siola, Amru; Antu, Evi Sunarti (Universitas Negeri Gorontalo, 2025)
Otanaha Regional Public Hospital is a Type C hospital located in Gorontalo Province. Existing issues at the hospital, such as poorly organized circulation, zoning that does not meet requirements, decentralized waste management, and inadequate facilities, serve as the basis for a redesign using a Sustainable Architecture approach. The design challenge is to identify an environmentally sustainable solution that balances the use of materials and energy while improving spatial organization and other environmental factors. The goal of this redesign is to develop a facility that aligns with the specifications and needs of the hospital, ensuring the implementation of physical construction that meets quality, time, and cost requirements, while also adhering to technical standards and building reliability regulations. The method used is an architectural design process incorporating a Sustainable Architecture approach. The resulting redesign incorporates features such as optimized natural lighting and ventilation through strategic placement of window openings and roof design, wastewater treatment for energy and water efficiency, integrated waste management, the selection of environmentally friendly materials, and the application of cultural preservation principles in the façade design, reflecting Gorontalo's cultural motifs.